Trends in Teaching English for Tourism: A Systematic Review (2013 -2022) - Desmayenni, Myra; Caniyago, Ako; Sitohang, Kommen Sohni; Arnaz, Dwi Fitri; Sutaryah, Cucu; Munifatullah, Feni (Jurnal Pendidikan Progresif, 2023)
Trends in Teaching English for Tourism: A systematic review (2013—2022). Objectives: This article provides the most research topics, strengths and limitations in teaching English for Tourism (EfT) for the last decade. Methods: This qualitative systematic review obtained the data from reputable open-access journals; totally 20 articles were scrutinized and classified. Findings: Models’ development in teaching EfT has become the most interesting topic since it contributes to sustainable studies due to the teaching EfT development. Meanwhile, the Corpus-based was preferable in the last decade for the EfT materials development. However, the scarcity of the studies in assessment and media might open a wide opportunity to be explored. Conclusion: Overall, the EfT teaching topics in the last ten years are categorized into models, materials, media and assessment. Future research with various innovations in teaching EfT, and further cooperation with tourism organizations and stakeholders can support stronger contribution to the success of teaching EfT. Keywords: english for tourism, trend, systematic review.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202302